Evaluation of Nutritional Status In Term of Selenium and Micro Nutrients of Maize Cultivation Lands in Sanliurfa Province - Aise DELIBORAN; Abdullah Suat NACAR (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
This study was conducted to determine the nutritional status of maize cultivated lands and maize plant in Sanliurfa province in term of selenium and micro elements. For this purpose, samples of soil and plants were taken from Sanliurfa province and Akcakale, Ceylanpinar, Harran and Viransehir districts. Texture, soil reaction, electrical conductivity, CaCO3, organic matter, available selenium, exchangeable iron, zinc, copper, manganese and boron analysis were done in the soil samples. Total iron, zinc, copper, manganese, selenium and boron content were determined in plants samples. According to results of soil and leaf analysis, nutritional problems in term of selenium have been determined in the lands of maize cultivation in all districts. Nutritional problem in term of zinc has been determined in only Ceylanpinar district, in term of copper has been determined in Ceylanpinar and Viransehir district. Considering the results of the work carried out in Sanliurfa; it is understood that effective fertilization programs, methods and fertilization time are extremely important. The quality and highly efficient production in the maize cultivation is related to balanced fertilization, addition of organic fertilizers and other technical applications.